Perpetually Aspiring: The Consequences of Poland’s Position in the Global Stratification of Science in the Context of the Debate on Research Evaluation - Remisiewicz, Łukasz (Studia Socjologiczne, 2026)
The author proposes a theoretical reinterpretation of the Polish debate on research evaluation, framing it as an effect of Poland’s position in the global stratification of science. The starting point is the interpretive hypothesis that Poland has a system located on the aspiring semi-periphery: dependent on external recognition, yet not permanently anchored at the centre of global science. Under such conditions, internationalization and metrics are not merely assessment techniques or neutral management tools. Rather, they become currencies of recognition and subjects of dispute over membership in the legitimate academic circuit. The author combines the concept of middle-status conformity with Randall Collins’s interaction ritual theory and the notion of metric capital to build an interpretive model explaining why aspiring systems exhibit a particular propensity to conform to the norms of the centre and, simultaneously, why the reactions of individual actors to reforms remain diverse. The argument relies on a reconstruction of the literature concerning the global stratification of science, Polish studies on evaluation, as well as a critical reading of regulatory documents and selected polemical texts. The result is the claim that the dispute over evaluation is better understood as a conflict between strategies for acquiring recognition.